GRAMMATICAL ERROR ANALYSIS IN WRITING NARRATIVE TEXTS (THE CASE OF STUDY AT THE X GRADE OF SMA NEGERI GUNUNG MERIAH, DELI SERDANG) ACADEMIC YEAR 2023/2024 - Jesi Martha Pristha; Sabrun Jamil; Wahyu Fatahillah (Tuwah Pande: Jurnal Ilmu Pendidikan dan Pengajaran, 2025)
Grammar is a component of English that must be learned by every English learner. An English learner can be said to be competent if they are able to write and speak English with proper grammar.Grammar mastery is very important in writing skill, it can help the students to produce good sentence. In writing text, students usually make a lot of grammatical errors in their writing. Grammatical error is anything where a sentence is structure incorrectly. In this research the reseacher doing a research about “Grammatical Error Analysis In Writing Narrative Texts ( The Case Of Study At The X Grade Of Sma Negeri Gunung Meriah Academic Year 2023/2024”. This research use descriptive qualitative reserch method and use descriptive analysis technique (percentage) with the percentage of information frequency and divided by the number of cases as a technique analysis data. Researchers took class X-IPS consisting of 29 students as a source of data in this study. Based on the research data obtained, researcher found that, from 29 students in class X-IPS, 13 (44.82%) students made errors in sentence patterns, 3 (10.34%) students made errors in the tenses section, 7 (24, 13%) of students made errors in writing pronouns, 18 (62.06%) students made mistakes in writing capital letters, 2 (6.89%) students made errors in writing or placing prepositions, and as many as 9 (31.06%) ) students make errors in spelling. Based on the data obtained, the most common grammatical errors or grammatical errors are found in capitalization, namely 62.06% and sentence patterns, namely 44.82%.